Awareness and Practices Towards Standard Precaution Among Nursing Staff - Haider, Nasira; Arshad, Faiza; Qayoum, Asma; Fatima, Arooj (Biological and Clinical Sciences Research Journal, 2025)
Standard precautions are fundamental in preventing healthcare-associated infections and safeguarding health-care workers and patients. As front-line providers, nurses must possess adequate knowledge and demonstrate appropriate practices to ensure effective infection control. Objective: To evaluate the awareness and practices regarding standard precautions among nurses and identify key factors influencing their adherence to these practices. Methods: This descriptive cross-sectional study was conducted at Medicare Hospital, Multan, from February 2024 to February 2025. One hundred full-time registered nurses in patient care were enrolled through convenience sampling. Data were collected using a structured questionnaire comprising three sections: incidence of exposure to infectious materials (8 items), knowledge of standard precautions (20 items), and self-reported practices (20 items). Sociodemographic details were also recorded. Descriptive statistics, t-tests, and multiple regression analyses were performed using SPSS version 22. Results: The mean knowledge score was 15.33 ± 2.20 out of 20. Nurses with a master’s degree scored significantly higher (17.08 ± 2.05) than those with a bachelor’s (15.11 ± 2.24; p = 0.003). Emergency room nurses had the lowest knowledge and practice scores compared to those in paediatrics and gynaecology. The mean practice score was 48.22 out of 80. Regression analysis revealed that knowledge score (β = 0.308) and years of experience (β = 0.187) were significant predictors of practice quality, explaining 20% of its variance (R² = 0.20). Conclusion: Nurses demonstrated high knowledge and satisfactory practices regarding standard precautions. Given the positive association between knowledge and practice, structured and recurrent training programs should be emphasised to enhance infection prevention behaviours among nursing staff.